Dyscalculia – one of the Types of Learning Disabilities - Tūbele, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is devoted to a theoretical justification of dyscalculia showing a link between characteristics of brain functions and expressions of learning disorders. Although dyscalculia and dyslexia are linked problems, the cognitive profile is different. Significant understanding of dyscalculia deals with origin and manifestations of it that affect learning in school and future quality of life. Development of neuroscience and brain studies performing magnetic resonance imaging (MRI), allow accurate descriptions of problem and in addition to search for ways to reduce the negative effects of dyscalculia.